Sistem Informasi Penjualan di Koperasi Karyawan Surya Menggunakan Model Waterfall - Risma Hardini; Hamid Muhammad Jumasa; Wahju Tjahjo Saputro (INTEK : Jurnal Informatika dan Teknologi Informasi, 2022)
Purworejo Muhammadiyah University's Surya co-worker, one of which is a chain store unit. In this unit, employees record and manage data of unconventional sales transactions. Receipts of cash payment information, the use of vouchers, and information for incoming and outgoing goods are made in writing on the transaction receipt sheet. It allows for record sales transactions to be damaged or lost. Furthermore, end-of-year report must collect all of the transaction records for a given time. Researchers built an information system on Purworejo Muhammadiyah University's Surya worker cooperative in the Purworejo business unit for processing data sales transactions of both members and nonmembers. Sis-tem development using the Waterfall Model. The methods of data collection that researchers use are observation, interviews, and library studies. This sales information system was built using the Framework Codeigniter 3. Based on the Black Box testing by using the Beta Method obtained an average percentage value of 82% which means a system built worthy to be used by employees in the store business unit on Purworejo Muhammadiyah University's Surya staff.